1992
DOI: 10.1016/0146-6380(92)90011-l
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of catalytic effects of indigenous minerals in the pyrolysis of Aleksinac oil shale organic matter

Abstract: The catalytic effect of indigenous minerals in the pyrolysis of Aleksinac (Yugoslavia) oil shale was studied in this paper. The substrates were prepared by gradual removal of the mineral constituents (carbonates, silicates, pyrite) and the free and bound bitumens. The substrates were analyzed by chemical methods, X-ray diffraction, porosimetry, thermal analysis, 13C NMR, and standard ASTM Micro Activity Test (MAT) designed for the investigation of cracking catalysts. The liquid pyrolysis products were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Espitalie et al [31] observed that this retention increases with the increase of clay content. Vucelic et al [32] also pointed out that alumina-silicates are mainly responsible for this sorption. However, when the oil shale mass loss is recalculated based on the pyrolyzed mass (organic matter content) (see Fig.…”
Section: Thermogravimetric Analysismentioning
confidence: 96%
“…Espitalie et al [31] observed that this retention increases with the increase of clay content. Vucelic et al [32] also pointed out that alumina-silicates are mainly responsible for this sorption. However, when the oil shale mass loss is recalculated based on the pyrolyzed mass (organic matter content) (see Fig.…”
Section: Thermogravimetric Analysismentioning
confidence: 96%
“…The promotion was greater than the inhibition in Fushun oil shale, which is the same as the conclusions of other researchers. 22,42–44 Meanwhile, this result provides corresponding theoretical basis for subsequent study of catalytic effect of silicates.…”
Section: Resultsmentioning
confidence: 75%
“…An important mass loss is observed in this temperature range. This stage is mainly attributed to the decomposition of bitumen and kerogen [15][16][17]. Under an inert atmosphere, the whole process is endothermic and the total mass loss is 27.96 %.…”
Section: Organic Matter Characterization Tg Dtg and Dsc Of Hungariamentioning
confidence: 99%